2005
DOI: 10.4049/jimmunol.175.9.5827
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell-Independent Antibody Response Promotes Resolution of Primary Influenza Infection and Helps to Prevent Reinfection

Abstract: It is generally believed that the production of influenza-specific IgG in response to viral infection is dependent on CD4 T cells. However, we previously observed that CD40-deficient mice generate influenza-specific IgG during a primary infection, suggesting that influenza infection may elicit IgG responses independently of CD4 T cell help. In the present study, we tested this hypothesis and show that mice lacking CD40 or CD4 T cells produce detectable titers of influenza-specific IgG and recover from influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
136
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 57 publications
13
136
0
1
Order By: Relevance
“…One report found increased mortality of SAP KO mice during chronic LCMV infection (8), but whether this was related to the Ab defect was not investigated. Our data show that SAP is not required for control of primary influenza infection, which is consistent with another report showing that mice deficient in T cell help due to CD40 deficiency or MHC class II deficiency control primary influenza infection as WT mice do (32). Despite control of primary infection, our data demonstrate that SAP is required for preventing secondary high dose influenza infection, and that IgG in serum from WT, but not SAP KO mice can protect mice against lethal infection.…”
Section: Discussionsupporting
confidence: 81%
“…One report found increased mortality of SAP KO mice during chronic LCMV infection (8), but whether this was related to the Ab defect was not investigated. Our data show that SAP is not required for control of primary influenza infection, which is consistent with another report showing that mice deficient in T cell help due to CD40 deficiency or MHC class II deficiency control primary influenza infection as WT mice do (32). Despite control of primary infection, our data demonstrate that SAP is required for preventing secondary high dose influenza infection, and that IgG in serum from WT, but not SAP KO mice can protect mice against lethal infection.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the virulence of the challenge virus is important. For example, even naive MT mice can clear the relatively avirulent X31 virus, but they rarely survive infection with the virulent PR8 virus (37). Thus, the importance of B cells in resistance to heterosubtypic infections is magnified by the dose and virulence of the challenge virus.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity against a primary infection with lethal type A influenza virus is to a large degree mediated by the humoral response, as shown by studies in which mice lacking B cells rapidly succumb to influenza infection despite the ability to mount a vigorous CD8 ϩ T cell response (1,2). Class switch recombination to Ab isotypes other than IgM is largely dependent upon T cell help, although Abs of the IgG isotypes are detectable at reduced titers in the absence of T-B interaction (3)(4)(5). Detailed analysis of the efficacy of Ab isotypes showed that IgG isotypes are primarily responsible for neutralizing influenza virus during primary and challenge infections (6,7), and earlier studies identified IgG2a as a key isotype for Ab-mediated effector functions in C57BL/6 mice (8 -10).…”
mentioning
confidence: 94%